The influence of brand image product quality and price on purchase decisions of garnier facial cleanser products in South Cikarang - Melissa Eka Murti Hartono; Primaraga Sumantri Indra Wicaksana (Enrichment : Journal of Management, 2023)
This study intends to investigate how brand image, product quality, and price affect consumers' decisions to buy Garnier facial washing soap. Quantitative research is the method employed. Nonprobability sampling using accidental sampling methodology is the sampling technique, and the sample size is 100 persons. The general populace in South Cikarang who use Garnier facial cleanser makes up the study's sample. Version 25 of SPSS software was utilized in this investigation. The analytical approach utilized included the tests for normality, multiple regression, the t test, and the coefficient of determination. The study's findings are as follows: Based on all of the aforementioned tests regarding the influence of brand image on purchasing decisions, the sig results are greater than 0.05, specifically 0.157, and the t-count value is 1.426 with a t-table less than 1.660, indicating that this has a negative impact on brand image but is not significant to purchasing decisions. Based on all the tests that have been conducted above regarding the impact of product quality on purchasing decisions, it is clear from the study's findings that there is a significant positive influence on product quality and that the sig value of 0.001 is less than 0.05 and that the calculated t value is 3.557 with the t table 1.660. Based on all of the tests that have been run to determine the impact of price on purchasing decisions, it is clear from the findings of this study that there is a positive and significant impact of price on those decisions. The calculated t value is 5.720 with t table 1.660, and the sig value of 0.000 is smaller than 0.05.